The usefulness of routine histopathology of bilateral nasal polyps – a systematic review, meta-analysis, and cost evaluation. Issue 1 (December 2015) - Wong, Jay SM; Hoffbauer, Stephanie; Yeh, David; Rotenberg, Brian; Gupta, Michael; Sommer, Doron
Abstract Background Controversy regarding the usefulness of routine histopathological examination of bilateral nasal polyps removed during endoscopic sinus surgery to identify occult diagnoses still exists. There is a paucity of high-level evidence in the literature. Methods A systematic review and meta-analysis was conducted. Two independent reviewers were used. Pooled proportions and numbers needed to screen were calculated. A cost per life year model was generated based on varying survival benefits and compared to other Canadian screening programs to provide financial context. Results Six studies (n = 3772 patients) were included. Of the 3772 patients, 3751 had a pre-operative clinical and post-operative pathological diagnosis of inflammatory nasal polyps. Agreement proportion was 99.44 %. There were 18 unexpected benign and three unexpected malignant diagnoses identified. This translated to a proportion of 0.48 and 0.08 % respectively. Number needed to screen was 210 and 1258 respectively. Pooled proportion for expected findings using a random effect model was 0.99 (95 % CI = 0.99–1). Pooled proportion for unexpected benign findings using a random effect model was 0.00522 (95 % CI = 0.00133–0.01). Pooled proportion for unexpected malignant findings using a random effect model was 0.00107 (95 % CI = 0.000147–0.00283). The cost to pick up one unexpected benign diagnosis was 14557.2. The cost to pick up 1 unexpected malignant diagnosis was 87204.56. Cost per quality life year calculated ranged from 3211.83 to 64677.58 based on varying assumptions on the survival benefits of identifying an unexpected malignancy. Conclusions Routine pathological examination in screening for neoplasia may be low yield, however, no compelling evidence was found to cease such practice. Surgeons should exercise individual judgment in requesting routine examination.